Financial Health Analyze of Building Construction Sub-Sector BUMN Companies on the Indonesian Stock Exchange Period 2020 – 2022 - Putri, Kartika Malika; Sam, Iskandar; Tiswiyanti, Wiwik (PT FORMOSA CENDEKIA GLOBAL, 2024)
This research aims to analyze the financial health of state-owned companies in the building construction sub-sector on the Indonesia Stock Exchange in 2020-2022 using 8 ratios, namely ROE, ROI, Cash Ratio, Current Ratio, Collection Periods, Inventory Turnover, Total Asset Turnover, and TMS to TA . The type of data used in this research is secondary data. This type of research is descriptive research with a quantitative approach. The results of the research show that PT Wijaya Karya received a BB rating in the